The contribution of Muslims to science during the Middle Abbasid Period (750-945) - Islam, Arshad (Kulliyyah of Science, IIUM, 2011)
A history of Muslims’ contribution to present-day science and technology is the exploration of the missing account of their glorious past. Muslims integrated science, theology, and philosophy as they were urged to study, acquire knowledge, and learn from others' expertise and civilization. The significance of this study lies not in recounting the specific contribution of Muslims to the individual disciplines of science such as medicine, mathematics, astronomy, geometry, geology, mineralogy, chemistry, philosophy and architecture, and trigonometry. Those accounts though greatly important in their own right have been the central focus of a number of works. This paper highlights those aspects of Muslims’ contribution to scientific body of knowledge that are subtle and perhaps more important to the development of the entire body of the scientific knowledge. Through an analysis of socio-cultural and historical context, the paper concludes that the contribution of Muslim scientist lies in (a) bringing to light the work of ancient Greek scholars in the field of science, and (b) bringing to the knowledge of Europe the works of Indian men of science, especially in mathematics, astronomy and medicine.